Comprehensive analysis of heat shock protein 110, 90, 70, 60 families and tumor immune microenvironment characterization in clear cell renal cell carcinoma - Wenjing Liao; Mao Huang; Xiaoyi Du; Liangdan Tang; Junwu Li; Qin Tang (Scientific Reports)
Abstract Heat shock proteins (HSPs) are a kind of molecular chaperone that helps protein folding, which is closely related to cancer. However, the association between HSPs and clear cell renal clear cell carcinoma (ccRCC) is uncertain. We explored the prognostic value of HSP110, HSP90, HSP70 and HSP60 families in ccRCC and their role in tumor immune microenvironment. The data obtained from the Cancer Genome Atlas (TCGA) were applied to determine the differential expression of HSPs in normal tissues and ccRCC. We comprehensively analyzed the prognostic value of HSPs in ccRCC and constructed a prognostic signature. We further explored the differences of tumor immune microenvironment and targeted therapy based on the signature. Cell proliferation, invasion and metastasis were detected by CCK8 assay, wound healing and transwell. Three clusters were identified with differences in overall survival and tumor stage. 6-gene signature (HSPA8, HSP90B1, HSPA7, HSPA12B, HSPA4L, HSPA1L) was identified to predict ccRCC patients’ prognosis. The signature was confirmed in the internal cohort. Survival analysis, receiver operating characteristic (ROC) curve, univariate and multivariate COX regression analysis demonstrated the accuracy and independence of signature. The expression of HSPA7, HSPA8 and HSP90B1 were validated with quantitative real-time PCR. Our signature played a pivotal role in predicting tumor immune microenvironment, immune checkpoint gene expression, drug sensitivity, and tumor mutational burden (TMB) in patients with ccRCC. Our cellular experiments confirmed HSPA7 promotes the proliferation, invasion and metastasis of ccCRC cells. The HSPs signature identified in this study could serve as potential biomarkers for predicting prognosis and treatment response in ccRCC patients. It may provide new ideas for the current research on targeted therapy and immunotherapy strategies for ccRCC patients.